Innovative Vocabulary Learning Through Games-Based Learning at SMKN 3 Parepare - Faradillah, Nurul; Sam Hermansyah; Isumarni; Yadinda Mahardika Darwis Putri; Septita Puteri Namirta; Eka Nanda Putri; Winda Aprilia; Hasprilia Putri; Nurhikmah (Universitas Muhammadiyah Enrekang, 2025)
Vocabulary is a fundamental aspect of language proficiency, serving as a critical foundation for communication, comprehension, and academic success. However, many vocational high school students face challenges in mastering English vocabulary due to teaching methods that often overlook individual differences in learning needs and abilities. This study explores the implementation of the